2006
DOI: 10.1016/j.febslet.2006.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation increases the invasive properties of hepatoma cells by destabilization of the adherens junction

Abstract: Tumor-associated macrophages play an important role in tumor progression, but whether they exert a tumor-progressive effect remains controversial. Here, we demonstrated that activated macrophage-conditioned medium (AMCM) obtained from RAW macrophages (RAW/AMCM) induced epithelial-mesenchymal transition (EMT) and stimulated the migratory and invasive activities of HepG2 cells, whereas control conditioned media had no effect. Epithelial-cadherin (E-cadherin) and b-catenin staining patterns were altered at the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 45 publications
6
55
1
1
Order By: Relevance
“…Our results have shown that culturing activated macrophages with A549 cells in the absence of TGF-β1 does not drive EMT however culturing activated macrophages with A549 cells in the presence of TGF-β1 accentuates TGF-β1 driven EMT. The results are in agreement with previously published reports demonstrating that conditioned media from activated tumour associated macrophages (TAMs) induced EMT and stimulated the migratory and invasive activities of hepatoma cells [49]. Furthermore, decreasing the number of TAMs markedly suppressed tumour growth and metastasis in breast cancer [50] suggesting that targeting TAMs in lung cancer may limit EMT and provide a novel therapeutic target.…”
Section: Discussionsupporting
confidence: 82%
“…Our results have shown that culturing activated macrophages with A549 cells in the absence of TGF-β1 does not drive EMT however culturing activated macrophages with A549 cells in the presence of TGF-β1 accentuates TGF-β1 driven EMT. The results are in agreement with previously published reports demonstrating that conditioned media from activated tumour associated macrophages (TAMs) induced EMT and stimulated the migratory and invasive activities of hepatoma cells [49]. Furthermore, decreasing the number of TAMs markedly suppressed tumour growth and metastasis in breast cancer [50] suggesting that targeting TAMs in lung cancer may limit EMT and provide a novel therapeutic target.…”
Section: Discussionsupporting
confidence: 82%
“…It is also important to note that a number of studies have analyzed the response of human cells to murine RAW 264.7 cells, with results that frequently replicate key features of disease pathology. [85][86][87][88][89][90][91][92][93] Future studies will use primary human macrophages to further develop this coculture system. Eventual testing of new therapeutics, particularly those targeting macrophage activation, using our developed coculture system will also be a key focus of future work.…”
Section: Discussionmentioning
confidence: 99%
“…In EMT there is a de-stabilization of adherent junctions [98] and the cells develop more invasive properties [93] .…”
Section: Hepatocarcinogenesis and Tumormicroenviromentmentioning
confidence: 99%